An international survey of patients living with spasticity. Issue 14 (3rd July 2017) - Barnes, Michael; Kocer, Serdar; Murie Fernandez, Manuel; Balcaitiene, Jovita; Fheodoroff, Klemens
Abstract: Purpose: To better understand patient perspectives on the life impact of spasticity. Methods: Global Internet survey (April 2014–May 2015) of 281 people living with spasticity. Results: Respondents indicated that spasticity has a broad impact on their daily-life: 72% reported impact on quality of life, 44% reported loss of independence and 44% reported depression. Most respondents (64%) were cared for by family members, of whom half had stopped working or reduced their hours. Overall, 45% reported dissatisfaction with the information provided at diagnosis; main reasons were "not enough information" (67%) and "technical terminology" (36%). Respondents had high treatment expectations; 63% expected to be free of muscle spasm, 41% to take care of themselves and 36% to return to a normal routine. However, 33% of respondents had not discussed these expectations with their physician. The most common treatments were physiotherapy (75%), botulinum neurotoxin (BoNT, 73%) and oral spasmolytics (57%). Of those treated with BoNT, 47% waited >1 year from spasticity onset to treatment. Conclusions: This survey emphasises the broad impact of spasticity and highlights unmet needs in the patient journey. Improvements with regards to communication and the therapeutic relationship would be especially welcomed by patients, and would help manage treatment expectations. Implications of Rehabilitation: Spasticity has broad impact on the lives of patients and their families that extends beyond the direct physical disability. Patients with spasticity need to be well informed about their condition and treatments available and should be given the opportunity to discuss their expectations. Physicians need to be aware of the patient's individual needs and expectations in order to better help them achieve their therapeutic goals.